k+4(2k-7)=-100

Simple and best practice solution for k+4(2k-7)=-100 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k+4(2k-7)=-100 equation:


Simplifying
k + 4(2k + -7) = -100

Reorder the terms:
k + 4(-7 + 2k) = -100
k + (-7 * 4 + 2k * 4) = -100
k + (-28 + 8k) = -100

Reorder the terms:
-28 + k + 8k = -100

Combine like terms: k + 8k = 9k
-28 + 9k = -100

Solving
-28 + 9k = -100

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '28' to each side of the equation.
-28 + 28 + 9k = -100 + 28

Combine like terms: -28 + 28 = 0
0 + 9k = -100 + 28
9k = -100 + 28

Combine like terms: -100 + 28 = -72
9k = -72

Divide each side by '9'.
k = -8

Simplifying
k = -8

See similar equations:

| (3/4)/(5/7) | | 2-5p-3p=-6 | | 3/4/5/7 | | -2m-24=0 | | 2-5p-4p=-6 | | 48/60 | | y+1=6/5x+18/5 | | a+4+2a=-8 | | -8n+-4=-28 | | (-3)*(-13)+(-41)= | | -11+2(x-3)+x=3(x-3)-8 | | 1=2+1/2 | | 5(3x+2)=2(2x+3) | | 5(x-2)-3=2x+3(-3+x) | | -5(7+7n)=-280 | | x/2+6=3x-12+x/2 | | 12x+15=-2 | | 3x+7=6x+9 | | 8n-4=-28 | | -6x-2x=-8 | | Y-2=4/9(x-3) | | 5x+5+1=-9 | | b+7+6=19 | | 5/6-1/3=-2 | | 3x+4x=12+16 | | -3x+5=6x+24 | | 4-4x-4=-20 | | 2-7x=-11x-5 | | 6y+4y=9y+8 | | 3x-12+5x+4=5x-28+7x+8 | | 1/4x+1/4=7/8 | | 7a-7=28a |

Equations solver categories